Post-transcriptional Regulation of BRCA2 through Interactions with miR-19a and miR-19b - Mogilyansky, Elena; Clark, Peter; Quann, Kevin; Zhou, Honglei; Londin, Eric; Jing, Yi; Rigoutsos, Isidore (Frontiers in Genetics, 2016)
Breast cancer type 2, early onset susceptibility gene (BRCA2) is a major component of the homologous recombination DNA repair pathway. It acts as a tumor suppressor whose function is often lost in cancers. Patients with specific mutations in the BRCA2 gene often display discrete clinical, histopathological and molecular features. However, a subset of sporadic cancers has wild type BRCA2 and display defects in the Homology-Directed Repair (HDR) pathway, which is the hallmark of ‘BRCAness’. The mechanisms by which BRCAness arises are not fully understood but post-transcriptional regulation of BRCA2 gene expression by microRNAs (miRNAs) may contribute to this phenotype. Here, we examine the post-transcriptional effects that some members of the six-miRNA cluster known as the miR-17/92 cluster have on the abundance of BRCA2’s messenger RNA (mRNA) and protein. We discuss two interactions involving the miR-19a and miR-19b members of the cluster and the 3´UTR of BRCA2’s mRNA. We investigated these miRNA:mRNA interactions in fifteen cell lines derived from pancreatic, breast, colon, and kidney tissue. We show that over-expression of these two miRNAs results in a concomitant decrease of BRCA2’s mRNA and protein expression in a subset of the tested cell lines. Additionally, using luciferase reporter assays we identified direct interactions between miR-19a/miR-19b and a miRNA response element (MRE) in BRCA2’s 3´UTR. Our results suggest that BRCA2 is subject to a complex post-transcriptional regulatory program that has specific dependencies on the genetic and phenotypic background of cell types.